Demystifying B3 drawbars - Carmon, Tim.; Morgan, P. J.; Safari eBooks ([S.l.] : Total Traing, 2009)
"During the past 50 years the Hammond B3 Organ has been and continues to be the keyboard instrument of choice for some of the greatest names in the world of music. However understanding the complexities and intricacies of this instrument has been an intimidating challenge for many. Join two of the greatest B3 keyboardists of all time, Tim Carmon and PJ Morgan, as they demystify how the drawbars are literally drawn and pulled in varying amounts toward the organ's console to create different harmonic sounds. Starting with the functionality of the drawbars and other controls of the organ, Tim and PJ demonstrate how different settings of the drawbars and other controls can give you literally millions of tonal qualities and endless shades of dynamic levels"--Resource description page.
Title from resource description page (viewed Sept. 23, 2009).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Electronic reproduction.
Keywords: Hammond B-3 organ; Organ (Musical instrument); B4 (Computer file); Electronic books